Variable rate fertilization system with adjustable active feed-roll length - Ning, Su; Taosheng, Xu; Liangtu, Song; Rujing, Wang; Yuanyuan, Wei (International Journal of Agricultural and Biological Engineering, 2015)
This paper presented a novel variable rate fertilization system based on the method of adjusting the active feed-roll length of a fluted roller. The feasibility of this method was discussed using analysis of the fluted roller model. One seed drill produced by Kuhn Company (France), which could sow and fertilize simultaneously, was used as a test platform to implement the mechanical structure of variable rate fertilization. The design methods for the variable rate fertilization mechanical structure and actuator were introduced in detail. A low-cost and stable embedded support decision subsystem and corresponding software were developed. The support decision subsystem is based on grid management. Each grid field cell contains information about corresponding spatial position and fertilizer application rate. A SpatiaLite database was employed to solve the spatial location search and spatial data query. Experiments were conducted to evaluate the fertilization uniformity and dynamic response time. The average value of coefficient of variation is 8.4% in five different active feed-roll lengths which reflects good uniformity. The dynamic response times for the adjustment of variable rate fertilization system from 204 kg/hm2 to 319 kg/hm2 and 319 kg/hm2 to 204 kg/hm2 are about 4.2 s. The results suggest that the variable rate fertilization system performs well in dynamic adjustment and stability.Keywords: precision agriculture, variable rate fertilization, fluted roller, active feed-roll length, servo drive, embedded systemDOI: 10.3965/j.ijabe.20150804.1644Citation: Su N, Xu T S, Song L T, Wang R J, Wei Y Y. Variable rate fertilization system with adjustable active feed-roll length. Int J Agric & Biol Eng, 2015; 8(4): 19－26.